(untitled) (Research, Society and Development, 2022)
The objective of this study was to analyze the principles and purposes belonged to education and human formation in contemporary times, with a view to understanding the educational concept configurations through socio-historical and cultural constructs, as well as how it fullfils men needs in his relationships with the world. It is a study of a qualitative nature, of the bibliographic type, in the light of the theoretical framework basically reconstructed in Plato and Kant. The premise that is established considers that the quality of human formation is involved in the principles and purposes attributed to education. Results showed meaningful contrasts between Platonic and Kantian educational concepts and current educational projects, in addition to raising reflections on the political and socioeconomic logic in contemporary training proposals, as well as the way they operate in modifying the basic values ​​of the formation of individuals. In view of this, the need to (re)think the revaluation of the educational process is reaffirmed with a view to overcoming the forms of alienation and conditioning imposed by the current political and economic systems.